Need for speed: Quality of innovations and the allocation of inventors - Santiago Caicedo; Jeremy Pearce (Federal Reserve Bank of New York, 2024)
This paper studies how the speed-quality tradeoff in innovation interacts with firm dynamics, concentration, and economic growth. Empirically, we document long-run trends in the increasing speed of innovation alongside declining quality at large firms. Leveraging variation from an exogenous policy change, we document the existence of the speed-quality tradeoff both at the firm and aggregate level. We develop an endogenous growth model that incorporates the speed-quality tradeoff and show that allocating less labor towards speed increases growth, particularly in the presence of private benefits to innovation and spillovers from heterogeneous innovations. We quantify the model to link firms' decisions across speed and quality to aggregate outcomes. Quantitatively, the recent growth slowdown is mainly due to changes in the innovation production function, while the allocation of inventors between speed and quality within firms has a modest impact. When spillovers across firms are taken into account, the effect becomes significantly larger; the shift to speed over the last 30 years explains up to one-quarter of the decrease in growth.
Keywords: O30; 031; O33; J63; 330; innovation; economic growth; slowdown; inventors; firm dynamics